Influence of water hardness on zinc toxicity in Daphnia magna. Issue 9 (21st March 2022) - Paylar, Berkay; Asnake, Solomon; Sjöberg, Viktor; Ragnvaldsson, Daniel; Jass, Jana; Olsson, Per‐Erik
Abstract: Zinc is an essential trace metal required for the maintenance of multiple physiological functions. Due to this, organisms can experience both zinc deficiency and toxicity. Hardness is recognized as one of the main modifying physiochemical factors regulating zinc bioavailability. Therefore, the present study analyzed the effect of hardness on zinc toxicity using Daphnia magna . Endpoint parameters were acute‐toxicity, development, reproduction, and expression data for genes involved in metal regulation and oxidative stress. In addition, the temporal expression profiles of genes during the initiation of reproduction and molting were investigated. Water hardness influenced the survival in response to exposures to zinc. A zinc concentration of 50 μg/l in soft water (50 mg CaCO3 /L) caused 73% mortality after 96 h exposure, whereas the same zinc concentration in the hardest water did not cause any significant mortality. Moreover, increasing water hardness from 100 to 200 mg CaCO3 /L resulted in a reduced number of offspring. Fecundity was higher at first brood for groups exposed to higher Zn concentrations. The survival data were used to assess the precision of the bioavailability models (Bio‐met) and the geochemical model (Visual MINTEQ). As the Bio‐met risk predictions overestimated the Zn toxicity, a competition‐based model to describe the effects of hardness on zinc toxicity is proposed. This approach can be used to minimize differences in setting environmental quality standards. Moreover, gene expression data showed that using the toxicogenomic approach was more sensitive than the physiological endpoints. Therefore, data presented in the study can be used to improve risk assessment for zinc toxicity. Abstract : The present study analyzed the effect of hardness on zinc toxicity using Daphnia magna for acute‐toxicity, development, reproduction, and gene expression. Results showed that hardness plays an important role for Zn toxicity by effectively changing the bioavailability of Zn. The competition between Zn, Ca, and Mg can be used to normalize hardness effect on mortality. Bioavailability models used in risk assessment could be improved by considering water hardness.